Autonomous power sharing for AC/DC HMGS using decentralized modified droop method for interlinking converter - Syed Abdul Razzaq; Vairavasamy Jayasankar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The present trend of integrating renewable energy sources (RES) in AC/DC hybrid micro grid systems (HMGS) has certainly reduced the greenhouse gases and provides the variety of power sources for micro grid (MG). Interlinking converter (ILC) is the main converter for interconnecting AC/DC sub-grids with a variety of features like autonomous bidirectional power sharing, reducing the power conversions in the grid and additionally a featuring aspect for energy management system (EMS). Interlinking converters are desired to maintain stable frequency, constant voltages at buses, reduce the power losses, reduce switching losses and control on circulating currents, most of the control methods could not achieve all. In this paper, the decentralized modified droop control method is presented which is significant in meeting the autonomous bidirectional AC/DC power load demand and in achieving the desired features. A three coordinated model is proposed where AC frequency, ILC power and DC voltage are the corresponding axis. The power sharing through the ILC is dependent on the AC frequency droop and DC voltage droop which occurs due to overloading. This control scheme is compatible for interconnection with multi-port grids. This control schemes provide more reliable, stable and accurate results compare to conventional droop methods.